Angiokeratoma of Fordyce treated with long pulsed Nd:YAG 1064 nm laser - Clarissa Prieto Herman Reinehr; Laura de Mattos Milman; Célia Luiza Petersen Vitello Kalil (Sociedade Brasileira de Dermatologia (SBD), 2020)
Introduction: Angiokeratoma of Fordyce are benign vascular lesions that present as small, asymptomatic, purple papule on the scrotum, shaft of the penis, or labia majora. Therapeutic options comprise several methods, including lasers. Case report: Men presented with multiple violaceous papules on the scrotum, compatible with angiokeratoma of Fordyce. The patient was treated with a single session of long pulsed Nd:YAG 1064 nm laser. Discussion: Treating angiokeratomas with lasers has the benefit of allowing vessel coagulation without bleeding. Conclusion: Even though these are benign lesions, patients seek treatment because of cosmetic concerns. Dermatologists should be aware of treatment options available.